2012
DOI: 10.1200/jco.2011.40.8120
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Platinum Concentration and Tumor Response in Non–Small-Cell Lung Cancer

Abstract: A B S T R A C T PurposePlatinum resistance is a major limitation in the treatment of advanced non-small-cell lung cancer (NSCLC). Reduced intracellular drug accumulation is one of the most consistently identified features of platinum-resistant cell lines, but clinical data are limited. We assessed the effects of tissue platinum concentrations on response and survival in NSCLC. Patients and MethodsWe measured total platinum concentrations by flameless atomic absorption spectrophotometry in 44 archived fresh-fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
71
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 33 publications
9
71
1
Order By: Relevance
“…Consistently, previous studies by Kim et al (9) and Tang et al (10) reported that decreased platinum accumulation in NSCLC tumor tissues and SCLC cells may be an important mechanism underlying platinum resistance in NSCLC and SCLC cells in the clinical setting.…”
Section: Introductionsupporting
confidence: 71%
“…Consistently, previous studies by Kim et al (9) and Tang et al (10) reported that decreased platinum accumulation in NSCLC tumor tissues and SCLC cells may be an important mechanism underlying platinum resistance in NSCLC and SCLC cells in the clinical setting.…”
Section: Introductionsupporting
confidence: 71%
“…Indeed, tissue platinum concentration is significantly associated with tumor response and survival in non-small cell lung cancer patients (13). Although OCTs play a critical role in the cellular uptake of platinum drugs, the relationship between OCTs and drug resistance is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The same relationship was seen individually in cisplatin and carboplatin groups. Patients with lower platinum concentration also had shorter time to recurrence, progression-free survival (PFS) and overall survival (OS) [ 7 ]. Furthermore, there was no signifi cant impact of potential variables such as the type of platinum compound, number of cycles, cumulative dose and time lapse from last chemotherapy, which strongly suggests that certain resistance-inducing transport factors, are likely modulating intratumoral platinum accumulation.…”
mentioning
confidence: 94%
“…Reduced uptake of cisplatin has also been demonstrated in resistant NSCLC cells [ 4 -6 ]. To clinically validate reduced drug accumulation as a signifi cant mechanism of platinum resistance in NSCLC, a recent study established correlation between intratumoral tissue platinum concentrations and tumor response in NSCLC [ 7 ]. A signifi cant relationship between tissue platinum concentrations and percent reduction in tumor size was demonstrated.…”
mentioning
confidence: 98%